Who is unbanked? Evidence from Poland - Rūta Banelienė; Borisas Melnikas (Contemporary Economics, 2019)
The objective of this article is to identify factors that exert an influence on the problem of unbanking in Poland. The empirical material used for the purposes of the presented study was obtained within the framework of the "Social Diagnosis" research project carried out in 2015 by the Board of Social Monitoring operating at the University of Finance and Management in Warsaw. Factors such as disposable personal income, age, one's level of education, trust placed in commercial banks, place of residence, population, and their social-occupational status had an influence on the propensity to use banking services. Answering the question put forward in the title of the paper, we found that the factors influencing people to remain unbanked were: young age, a low level of education, low income, living in small towns/cities, and lack of trust in commercial banks. The paper contributes to the advancement of research on financial exclusion by providing knowledge on the factors that seem to have an impact on its acceptance on the market in Poland.
Keywords: D14; G21; 330; Unbanked; Banking services; Financial exclusion